"My Fibro Family!" A qualitative analysis of facebook fibromyalgia support groups' discussion content. Issue 1 (31st December 2022) - Crump, Lyndsay; LaChapelle, Diane
ABSTRACT: Background: Fibromyalgia (FM) is a diagnostically controversial syndrome characterized by chronic widespread pain, fatigue, sleep difficulties, cognitive dysfunction, and mental health symptoms. Though online peer support groups (OPSGs) may help persons with FM access support and information, there are concerns that such groups can be harmful. Aims and Methods: Using a nonparticipatory observational stance, the authors analyzed discussions in three Facebook FM OPSGs (approximately 15, 000 members, mostly women) to determine what themes best characterize their discussion content and whether being in a particular group was related to the type of thematic content to which they were exposed. Results: Two themes were identified that represented explicit reasons group members participated in the OPSG (trying to understand FM and seeking/offering emotional support). Six themes represented underlying reasons members sought informational and emotional support in FM OPSGs (fighting FM, learning to live with FM, struggling with identity, distressing thoughts and feelings, judgment, empowerment-seeking). No salient differences were identified between the thematic content of each group. Conclusions: The findings suggest that FM OPSGs may provide much needed psychosocial and emotional support regarding important aspects of psychological adjustment to living with FM while also inadvertently encouraging approaches to living with FM that do not align with evidence-based FM management recommendations (e.g., investment in fighting rather than accepting FM). These findings may be useful to patients considering joining an FM OPSG and to health providers helping patients navigate to resources that can address their emotional or psychological support needs.